2020
DOI: 10.1098/rspb.2019.2292
|View full text |Cite
|
Sign up to set email alerts
|

Redirection of ambient light improves predator detection in a diurnal fish

Abstract: Cases where animals use controlled illumination to improve vision are rare and thus far limited to chemiluminescence, which only functions in darkness. This constraint was recently relaxed by studies on Tripterygion delaisi , a small triplefin that redirects sunlight instead. By reflecting light sideways with its iris, it has been suggested to induce and detect eyeshine in nearby micro-prey. Here, we test whether ‘diurnal active photolocation’ also improves T. delaisi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…When released on the gravel lane, triplefins immediately started to show fin flicks and bobs while carefully approaching the display compartment. This is consistent with previous laboratory and field experiments that showed that a differentiated response between visual stimuli can be observed very soon after release in the experimental tank (Santon et al., 2020). Based on these tests, we set the observation time at 10 min for each stimulus.…”
Section: Methodssupporting
confidence: 93%
See 2 more Smart Citations
“…When released on the gravel lane, triplefins immediately started to show fin flicks and bobs while carefully approaching the display compartment. This is consistent with previous laboratory and field experiments that showed that a differentiated response between visual stimuli can be observed very soon after release in the experimental tank (Santon et al., 2020). Based on these tests, we set the observation time at 10 min for each stimulus.…”
Section: Methodssupporting
confidence: 93%
“…Triplefins were gently released in the middle of the gravel lane and, during the subsequent 10 min, a single observer (FD) counted the number of bobs and fin flicks observed in one‐minute intervals and noted the distance from the tip of triplefins’ snout to the stimulus at the end of each full minute. Other typical behaviors in T. delaisi such as bright spots of focussed light on the iris, termed ocular sparks (Michiels et al., 2018; Santon et al., 2020), and tail flicks (Wirtz, 1978) were also noted, but ignored in the analysis due to their very low frequencies. Before each 10‐min session, the focal triplefin was temporarily placed in a dark container for 5 min while the visual stimulus was put in place.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this small light source next to the pupil is weak, its close alignment with the visual axis makes it sufficiently strong to induce perceivable reflections in the reflective eyes of target organisms. Recently, we showed that this mechanism can contribute to the visual detection of the retroreflective eyes of cryptic, predatory scorpionfish (Santon et al ., 2018, 2020). Whether active sensing with light or diurnal active photolocation contributes to prey detection has not yet been experimentally demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that micropredatory fish are able to redirect enough downwelling sunlight sideways to illuminate and thus improve visual detection of nearby organisms (Bitton et al, 2019;Santon et al, 2020). This suggestion follows the simple observation that a small amount of light suffices to generate a perceivable increase in eyeshine in the pupils of species with retroreflective eyes, provided the observer possesses a (small) light source near-coaxial to its viewing axis, for example on its iris (Jack, 2014(Jack, , 2015Santon et al, 2018).…”
mentioning
confidence: 99%